Sakrament namaszczenia chorych a dzieci, które nie osiągnęły używania rozumu, oraz osoby od urodzenia upośledzone umysłowo - Bartoszek, Antoni (Studia Pastoralne, 2026)
Relying on the Code of Canon Law which states that „[t]he anointing of the sick can be administered to a member of the faithful who, having reached the use of reason, begins to be in danger due to sickness or old age” (CCL Can. 1004 §1), the author of the present article aims at proving that, from the theological point of view, there are no contraindications against administering this sacrament to seriously ill persons who, with all certainty, haven’t reached the use of reason and whose loved ones ask for it with faith. This problem concerns very small children and the mentally disabled from birth. On the basis of careful biblical, historical and theological analysis, it has become clear that the penitential dimension of Anointing of the Sick is not primary, and as such is not an obstacle to confer this sacrament on those who, having been baptized, have not reached the use of reason and do not bear the personal guilt. The act of faith, which is essential in all sacraments and which is required on the part of the recipients, can be realized through the fact that the sacrament is administered in an environment of faith surrounding ill children or the mentally disabled. The act of conferring this sacrament to them is a sign of their unity with Christ, crucified and risen, and will serve as a spiritual strengthening for their loved ones.